Stomata and Sporophytes of the Model Moss Physcomitrium patens - Caine, Robert S.; Chater, Caspar C. C.; Fleming, Andrew J.; Gray, Julie E. (Frontiers in Plant Science, 2020)
Mosses are an ancient land plant lineage and are therefore important in studying the evolution of plant developmental processes. Here, we describe stomatal development in the model moss species Physcomitrium patens (previously known as Physcomitrella patens) over the duration of sporophyte development, dissect the molecular mechanisms guiding cell division and fate and highlight how stomatal function might vary under different environmental conditions. In contrast to the asymmetric entry divisions described in Arabidopsis thaliana, moss protodermal cells can enter the stomatal lineage directly by expanding into an oval shaped guard mother cell (GMC). We observed that when two early stage P. patens GMCs form adjacently, a spacing division can occur, leading to separation of the GMCs by an intervening epidermal spacer cell. We investigated whether orthologues of Arabidopsis stomatal development regulators are required for this spacing division. Our results indicated that bHLH transcription factors PpSMF1 and PpSCRM1 are required for GMCs formation. Moreover, the ligand and receptor components PpEPF1 and PpTMM are also required for orientating cell divisions and preventing single or clustered early GMCs from developing adjacent to one another. The identification of GMC spacing divisions in P. patens raises the possibility that the ability to space stomatal lineage cells could have evolved before mosses diverged from the ancestral lineage. This would have enabled plants to integrate stomatal development with sporophyte growth and could underpin the adoption of multiple bHLH transcription factors and EPF ligands to more precisely control stomatal patterning in later diverging plant lineages. We also observed that when P. patens sporophyte capsules mature in wet conditions, stomata are typically plugged whereas under drier conditions this is not the case; instead, mucilage drying leads to hollow sub-stomatal cavities. This appears to aid capsule drying and provides further evidence for early land plant stomata contributing to capsule rupture and spore release.